Needs and Need Responses of Preoperative Patients in Mahasarakham Hospital - Yusamran, Maniga; Gawgleun, Wasan (Journal of The Royal Thai Army Nurses, 2021)
The purpose of this descriptive research was to examine needs and need responses of preoperative patients in Mahasarakham Hospital. The sample consisted of 370 preoperative patients undergoing major surgery in Mahasarakham Hospital and met the study inclusion criteria. Select a specific sample group with the qualifications: 1) being 20 years of age or over both male and female 2) are patients in the preoperative period, surgery department and gynecology department 3) patients who are treated with elective case. Research instruments included the patient’s demographic questionnaire, the Preeyaporn samakkan’s needs and need responses questionnaire which were developed based on Gaglione’s concept. Data were analyzed using descriptive statistics and paired t-test. The results revealed that 1) The overall score of needs was at a high level ( = 51.88, SD = 6.86). 2) The overall score of need responses was at low level ( = 10.70, SD = 5.97) and 3) Paired t-test showed a significantly significant difference between overall needs and need responses from preoperative nursing score for patients undergo major surgery (t = 89.71, p < .001). The mean total score of needs among preoperative patients was significantly higher than those of need responses. These finding suggest that nurses can be use the result to improve quality of preoperative nursing that focuses on emotional and spiritual needs of patients to meet demands effectively and comprehensively.